Gene Editing: How Can You Ask "Whether" If You Don't Know "How"?. Issue 3 (24th May 2021) - Cwik, Bryan
Abstract: Though questions about whether gene editing should be done at all have dominated ethical discussion, a literature about how it can be done ethically has been growing. Work on responsible translational pathways for human germline gene editing has been criticized for focusing on the wrong questions. But questions about responsible translational pathways—questions about how gene editing could be done ethically—are, in an important sense, prior to questions about whether it is desirable and permissible. Asking "whether" questions about gene editing requires a model of what responsible clinical use of gene editing would look like .